Letter - Brooke, Eileen E.
1939-07-18 038-0080-001 46 Kingsway London W.C.2 Tel Holborn 6535 July 18th., 1939. Your ref: International. HVT/AEC/MS/1.425. Dear Mr. Tewson, Thank you for your letter of the 17th. inst., regarding Ana María Gallut Fernández. It was most kind of you to take so much trouble over the case of this child, and, as you say, in the face of her father's express request, the only possible course was to send her back to her parents. With renewed thanks, I remain, Yours sincerely, Eileen E. Brooke. Secretary to Don Pablo Azcárate. H.V. Tewson, Esq., Trades Union Congress, Transport House, Smith Square, S.W.1. 292/946/38/80(I)